2015
DOI: 10.5500/wjt.v5.i4.329
|View full text |Cite
|
Sign up to set email alerts
|

Excellent long term patient and renal allograft survival after ABO-incompatible kidney transplantation: Experience of one center

Abstract: AIM:To investigate the long-term results of ABOincompatible (ABOi) kidney transplantation in a single center in Greece. Melexopoulou C et al . ABO-incompatible kidney transplantation or mycophenolate acid was administered. We compared the long term results of our ABOi group to those of a matched group of 30 ABO compatible (ABOc) living kidney recipients with similar baseline characteristics. The ABOc recipients received an immunosuppressive regimen consisting of TAC and mycophenolate acid. All patients in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Results of a study showed that ABO‐incompatible kidney transplantation is a safe and effective therapeutic strategy. The long‐term patient and graft survival rates are excellent and do not differ significantly from the control group 38 . Takahashi et al also found that rates of graft survival in recipients of ABO‐incompatible living kidney transplants are similar to those in recipients of ABO‐compatible grafts and that transplantation of ABO‐incompatible kidneys from living donors is a radical, but effective treatment for ESRD 39 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Results of a study showed that ABO‐incompatible kidney transplantation is a safe and effective therapeutic strategy. The long‐term patient and graft survival rates are excellent and do not differ significantly from the control group 38 . Takahashi et al also found that rates of graft survival in recipients of ABO‐incompatible living kidney transplants are similar to those in recipients of ABO‐compatible grafts and that transplantation of ABO‐incompatible kidneys from living donors is a radical, but effective treatment for ESRD 39 .…”
Section: Discussionmentioning
confidence: 95%
“…The long-term patient and graft survival rates are excellent and do not differ significantly from the control group. 38 Takahashi et al also found that rates of graft survival in recipients of ABO-incompatible living kidney transplants are similar to those in recipients of ABO-compatible grafts and that transplantation of ABO-incompatible kidneys from living donors is a radical, but effective treatment for ESRD. 39 Sivakumaran et al concluded that there did not seem to be any association between donor and recipient ABO type in relation to ABMR.…”
Section: Abmrmentioning
confidence: 91%
“…All of these findings on the higher mortality rate in transplants involving ABOi, probably related to the side effects of high immunosuppression are in favor of tailored immunosuppression. Indeed, some studies in which selected patients received a lower, tailored desensitization therapy reported an improved survival rate, with fewer infections and without ABMR[ 52 - 54 ].…”
Section: Clinical Outcomes After Renal Transplantation Involving Aboimentioning
confidence: 99%